2020
DOI: 10.1002/advs.202001714
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform Metabolomics Reveals Novel Serum Metabolite Biomarkers in Diabetic Retinopathy Subjects

Abstract: Diabetic retinopathy (DR) is the main cause of vision loss or blindness in working age adults worldwide. The lack of effective diagnostic biomarkers for DR leads to unsatisfactory curative treatments. To define potential metabolite biomarkers for DR diagnosis, a multiplatform-based metabolomics study is performed. In this study, a total of 905 subjects with diabetes without DR (NDR) and with DR at different clinical stages are recruited. Multiplatform metabolomics methods are used to characterize the serum met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 38 publications
4
59
4
Order By: Relevance
“…We found that the arachidonic acid metabolites such as hydroxyeicosatetraenoic acids (HETEs) and leukotriene, which are known mediators for DR development [20,21], were increased in the fecal of PDR patients, making them as the potential diagnostic markers and therapeutic targets. Our results were consistent with previous studies that HETEs were also increased in the serum of DR patients as compared to NDR patients [22]. On the other hand, there were 34 fecal metabolites including Vanillate, D-galactonate, D-gluconic acid and Aerobactin that were signi cantly enriched in microbial metabolism, showing an extensive interplay between the gut microbiota and the host through metabolic exchange and substrate co-metabolism [23].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the arachidonic acid metabolites such as hydroxyeicosatetraenoic acids (HETEs) and leukotriene, which are known mediators for DR development [20,21], were increased in the fecal of PDR patients, making them as the potential diagnostic markers and therapeutic targets. Our results were consistent with previous studies that HETEs were also increased in the serum of DR patients as compared to NDR patients [22]. On the other hand, there were 34 fecal metabolites including Vanillate, D-galactonate, D-gluconic acid and Aerobactin that were signi cantly enriched in microbial metabolism, showing an extensive interplay between the gut microbiota and the host through metabolic exchange and substrate co-metabolism [23].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, amino acid metabolism serves as the connecting bridge of DR-altered metabolic network and many amino acids are altered signi cantly in DR patients. It is reported that the glycine, serine and threonine metabolism is the most enriched pathway, which reproduces the results of a recent metabolomics research (10). According to Rajala et al (30), serine and glycine residues can stabilize the Warburg-like effect by enriching the photoreceptor protein rhodopsin, which is closely associated with the phosphorylation of pyruvate kinase M2.…”
Section: Discussionsupporting
confidence: 81%
“…Fortunately, Li et al (12) and Chen et al (13) have suggested that serum metabolic pro les will alter the metabolic pathways associated with DR. Furthermore, Xuan et al (10) report that 12-hydroxyeicosatetraenoic acid (12-HETE) and 2-piperidone may serve as diagnostic markers of DR and further emphasize the value of serum metabolomics studies for ascertaining its pathogenesis. Though above-mentioned metabolomics studies are devoted to nding DRrelated biomarkers, research on the mechanism of DR is still limited, which might be due to the incomplete existing metabolic pathways map as well as improper application of threshold-based pathway analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of modern biological analysis technology, metabolomics has been successfully applied in many fields, such as cancer research ( Tayanloo-Beik et al, 2020 ). Metabolomics is one of the “omics” techniques, and is complementary to genomics, transcriptomics, and proteomics ( Xuan et al, 2020 ). Metabolites are defined as small organic and low-molecular-weight compounds (<1,500 Dalton), which are the final products during the metabolic process ( Alonso et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%